Identifying nutritional and life-style risk factors associated with the development of osteoporosis in women of Asian origin at the Aga Khan University Hospital, Nairobi, Kenya - Chaudhri, Tauseef (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2006.